Penerapan Metode Heuristic Evaluation Pada Sistem Informasi Kontrasepsi Rasional (SIKONTRAS) - Ita Permatahati; Rahmad Ardhani (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
The SIKONTRAS application is a web-based application that has previously been used to socialize contraceptives to support government programs in broadcasting family planning programs, however, with technological developments and the large number of user demands who want comfort and ease in accessing information with attractive visuals, especially in terms of system appearance. used, the author took the initiative to carry out an evaluation of the SIKONTRAS application by going through the initial stages, namely distributing questionnaires to SIKONTRAS users and experts in the field of information system development, then from the results of the assessment, they will then be analyzed using the heuristic evaluation method. The research method is heuristic evaluation, method to identify design problems in user interfaces. The evaluator assesses the design based on a set of guidelines (called heuristics) that make the system easy to use. This Heuristic Evaluation is used to obtain usability testing results from SIKONTRAS. Testing was carried out on 5 respondents in the IT sector and the process included the following stages in carrying out the test. Based on the results of data analysis using heuristic evaluation, it can be concluded that the evaluation results of the SIKONTRAS system contained the greatest value in the flexibility and efficiency of use variable indicators, which means SIKONTRAS is flexible in using the system and easy for new users to understand, but development recommendations are still given based on comments and input by respondents, where respondents have professions in the field of information systems.